OPTIMIZATION OF SOLID-PHASE SYNTHESIS OF POLYAMIDE NUCLEIC ACID MIMETICS WITH APPLICATION OF MALDI-TOF MASS-SPECTROMETRY - M. V. Shirayeva; Yu. G. Kirillova; E. D. Nikol’Skaya; D. I. Prokhorov; I. P. Smirnov; G. E. Pozmogova (Тонкие химические технологии)
The solid-phase synthesis of a tetrameric model sequence of polyamide nucleic acid mimetics (PANAM) incorporating terminal chiral and charged unit was performed. As a result during the synthesis and cleavage from the resin the tendency of PANAM with the N-terminal negatively charged monomer to cyclization with simultaneous N-acyl transfer of carboxyethyl base residue was found. Application of MALDI-TOF mass - spectrometry allowed us to find suitable conditions for obtaining PANAM oligomers without the significant amount of by-products.